TANTANGAN DAN STRATEGI IMPLEMENTASI CHATBOT GOVERNMENT TRANSFORMASI ADMINISTRASI DIGITAL DI INDONESIA - Sasfiani, Serly; Putra, Raniasa; Imania, Katriza; Iriani, Atrika (Universitas Padjadjaran, 2025)
Transformed modern governance, particularly through the implementation of government chatbots as a public policy instrument. This study employs a literature review method with Winter’s Policy Implementation Model framework to analyze the opportunities and challenges of adopting government chatbots in Indonesia. The analysis reveals that successful implementation depends heavily on strong inter-organizational collaboration, readiness of lower-level bureaucracy, and digital literacy and access among target communities. Key challenges include limited digital infrastructure, technological access disparities, low human resource competencies, and regulatory and ethical issues concerning privacy and algorithm transparency. A comprehensive implementation strategy involves strengthening national data integration, enhancing human resource capacity, adaptive regulation, multi-stakeholder collaboration, and prioritizing digital security and sovereignty. AI implementation via government chatbots has the potential to revolutionize public governance towards inclusive, efficient, and responsive smart governance. The main challenges include limited digital infrastructure, unequal access to technology, low human resource competency, as well as regulatory and ethical issues related to privacy and algorithm transparency. A comprehensive implementation strategy includes strengthening national data integration, increasing human resource capacity, adaptive regulations, multi-party collaboration, as well as prioritizing digital security and sovereignty. The implementation of AI through government chatbots has the potential to revolutionize public governance towards smart governance that is inclusive, efficient and responsive to community needs. This research concludes that with the right strategy, the implementation of chatbot government can be optimized to support Electronic-Based Government Systems (SPBE) and accelerate the realization of more responsive and efficient public administration in Indonesia. Penelitian ini bertujuan untuk menganalisis dan mengidentifikasi tantangan-tantangan utama serta merumuskan strategi yang efektif dalam mengimplementasikan chatbot pemerintah (GovChatbot) dalam rangka transformasi administrasi digital di Indonesia. Fokus utamanya adalah pemanfaatan kecerdasan buatan (AI) untuk meningkatkan efisiensi dan kualitas pelayanan publik. Metode yang digunakan kemungkinan besar melibatkan pendekatan kualitatif, seperti studi literatur, analisis dokumen kebijakan (misalnya, Perpres No. 95 Tahun 2018 tentang SPBE), atau studi kasus di beberapa instansi pemerintah yang telah menerapkan layanan digital. Data dikumpulkan melalui kajian pustaka, wawancara, atau observasi, dan dianalisis untuk memahami dinamika implementasi di lapangan. Hasil analisis menunjukkan bahwa keberhasilan implementasi sangat bergantung pada sinergi hubungan antarorganisasi, kesiapan birokrasi level bawah, serta kesiapan dan literasi digital masyarakat sebagai kelompok sasaran. Tantangan utama meliputi keterbatasan infrastruktur digital, ketimpangan akses teknologi, rendahnya kompetensi SDM, serta isu regulasi dan etika terkait privasi dan transparansi algoritma. Strategi implementasi yang komprehensif meliputi penguatan integrasi data nasional, peningkatan kapasitas SDM, regulasi adaptif, kolaborasi multipihak, serta prioritas keamanan dan kedaulatan digital. Implementasi AI melalui chatbot government berpotensi merevolusi tata kelola publik menuju smart governance yang inklusif, efisien, dan responsif terhadap kebutuhan masyarakat. Penelitian ini menyimpulkan bahwa dengan strategi yang tepat, implementasi chatbot government dapat dioptimalkan untuk mendukung Sistem Pemerintahan Berbasis Elektronik (SPBE) dan mempercepat terwujudnya administrasi publik yang lebih responsif dan efisien di Indonesia.